Tuning of Novel Fractional Order Fuzzy PID Controller for Automatic Voltage Regulator using Grasshopper Optimization Algorithm - Mohammad Ali Khaniki; Mohammad Hadi; Mohammad Manthouri (Majlesi Journal of Electrical Engineering)
One of the most important equipment in the power system is the Automatic Voltage Regulator (AVR) or synchronous generator excitation. The goal of the system is to maintain the terminal voltage of the synchronous generator in the desired level. AVR is inherently uncertain. Hence, the proposed controller should be able to handle the problem. In this paper, Fractional Order Fuzzy PID (FOFPID) controller has been employed to control the system. In order to enhance the performance of the controller, Grasshopper Optimization Algorithm (GOA) is used to tune the parameters of the controller. Unlike other methods, the gains of FOFPID controller are not constant and alter in different operating conditions. The robustness of the controller has been investigated and the comparative results show that the proposed controller has a better performance against other methods.Automatic Voltage Regulator (AVR), Synchronous generator excitation, Fractional-order fuzzy PID (FOFPID) controller, Grasshopper Optimization Algorithm (GOA), Uncertainty